1999
DOI: 10.1002/(sici)1099-1085(19990228)13:3<423::aid-hyp747>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Microthermal gradients and ecological implications in Dorset rivers

Abstract: Microthermal gradients, involving signi®cant variations in temperature over distances of a few centimetres to a few metres, were investigated in the water column and substratum of the River Frome and Bere Stream in Dorset, UK, which are groundwater dominated streams fed by chalk aquifers. In many of the sections surveyed, strong lateral contrasts of up to c. 7 8C were evident as a consequence of solar heating of shallow channel margin zones and thin surface layers isolated by¯oating vegetation from the main bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…The consideration of streambed heat flux in 1998 at Catamaran Brook, where limited data were available, showed that an improvement of less than 0.1°C could be achieved with the consideration of streambed fluxes. Groundwater and geothermal contributions have been observed to modify the thermal regime of rivers as reported in other studies (Clark et al, 1999). Heat flux at the sediment water interface has also been shown to be a contributing factor (Comer and Grenney, 1977;Hondzo and Stefan, 1994).…”
Section: Discussionsupporting
confidence: 66%
“…The consideration of streambed heat flux in 1998 at Catamaran Brook, where limited data were available, showed that an improvement of less than 0.1°C could be achieved with the consideration of streambed fluxes. Groundwater and geothermal contributions have been observed to modify the thermal regime of rivers as reported in other studies (Clark et al, 1999). Heat flux at the sediment water interface has also been shown to be a contributing factor (Comer and Grenney, 1977;Hondzo and Stefan, 1994).…”
Section: Discussionsupporting
confidence: 66%
“…The influence of substrate type on diel temperature fluctuations is very dramatic in WS 3 because of the homogeneity of each reach type and the volume of water exposed to each substrate type. Most streams have high heterogeneity of substrate conditions, which may explain why the influence of specific substrates on in-stream temperature dynamics is not broadly recognized (i.e., Clark et al 1999).…”
Section: Substrate Influences On Stream Temperaturesmentioning
confidence: 99%
“…Dampening of subsurface diurnal water temperatures has been documented as a function of depth into subsurface gravels (Ringler and Hall 1975;Evans et al 1998;Malcolm et al 2002). Influences of hyporheic exchange flows on surface stream temperatures have generally been observed only at microscales, such as upwelling locations or within small side channels (White et al 1987;Evans et al 1998;Clark et al 1999), creating important thermal refugia for biota.…”
Section: Substrate Influences On Stream Temperaturesmentioning
confidence: 99%
“…Another factor explaining the coincidence of the temperature and net shortwave radiation peaks is the shallowness of Fryxell Basin streams, typically less than 0.3 m. Vugts reported the rapid response of a small stream to meteorological conditions [53], and a study by Clark et al showed that water in shallow areas along the channel margins reached maximum and minimum daily temperatures an average of 180 and 100 min earlier, respectively, than water in the main channel [9]. Shallow depths may play a role in localized areas of heat gain in Von Guerard Stream.…”
Section: Processes and Factors Influencing Streamwater Warming: Radiamentioning
confidence: 99%